The role of the Algerian school in preventing the spread of drug phenomenon:A field study from the point of view of average managers in Tamanrasset - Benlahbib, Sidahmed; Hadad, Yasmina (Social Empowerment Journal, 2021)
This study came to provide objective explanations of the reality of drug use in educational institutions, especially in the averages, i.e. the school, which is one of the institutions of socialization, which has an active role in meeting the needs of students and educating them, and works to raise awareness, awareness and prevention of the dangers of the spread of this social scourge, which has spread throughout the world and not only in our society, and has not been able to date any institution or organization, whether international or social institution, to reduce this phenomenon. We have limited this study to the level of the directors of the average city of Tamanrasset, according to the average managers using the descriptive method. Where this study concluded that the Algerian school carries out follow-up, control and sensitization to prevent the spread of drug phenomenon among students.